Key differences in regulation of opioid receptors localized to presynaptic terminals compared to somas: Relevance for novel therapeutics. (15th March 2023) - Coutens, Basile; Ingram, Susan L.
Abstract: Opioid receptors are G protein-coupled receptors (GPCRs) that regulate activity within peripheral, subcortical and cortical circuits involved in pain, reward, and aversion processing. Opioid receptors are expressed in both presynaptic terminals where they inhibit neurotransmitter release and postsynaptic locations where they act to hyperpolarize neurons and reduce activity. Agonist activation of postsynaptic receptors at the plasma membrane signal via ion channels or cytoplasmic second messengers. Agonist binding initiates regulatory processes that include phosphorylation by G protein receptor kinases (GRKs) and recruitment of beta-arrestins that desensitize and internalize the receptors. Opioid receptors also couple to effectors from endosomes activating intracellular enzymes and kinases. In contrast to postsynaptic opioid receptors, receptors localized to presynaptic terminals are resistant to desensitization such that there is no loss of signaling in the continuous presence of opioids over the same time scale. Thus, the balance of opioid signaling in circuits expressing pre- and postsynaptic opioid receptors is shifted toward inhibition of presynaptic neurotransmitter release during continuous opioid exposure. The functional implication of this shift is not often acknowledged in behavioral studies. This review covers what is currently understood about regulation of opioid/nociceptin receptors, with an emphasis on opioid receptor signaling in pain and reward circuits. Importantly, the review covers regulation of presynaptic receptors and the critical gaps in understanding this area, as well as the opportunities to further understand opioid signaling in brain circuits. This article is part of the Special Issue on "Opioid-induced changes in addiction and pain circuits". Highlights: Opioid receptors are highly regulated through desensitization, internalization and recycling processes. Presynaptic opioid and nociceptin receptors are resistant to desensitization compared to postsynaptic receptors. Consequences of desensitization and internalization are dependent on the local environment and receptor-effector coupling. Opioid receptor-effector coupling is altered with continued administration of agonist.